Experimental and computational approaches to investigate the high oxidation state oxo- and hydroxido- redox chemistry of osmium - Van Niekerk, Daniel Malan Emmanuel (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.